Empowering Women Through Islamic Philanthropy: An Exploration on Islamic Social Finance Towards Women’s Employment In Nigeria - Tijjani Muhammad; Fahd Al-Shaghdari (Program Studi Ekonomi Syariah, FEBI UIN Datokarama Palu, 2025)
Women’s unemployment remains a critical challenge in many Muslim-majority regions, including Northern Nigeria, where socio-cultural barriers and limited access to financial resources constrain women’s economic participation. Despite growing discourse on Islamic social finance, empirical evidence on its effectiveness in promoting women’s employment remains limited, particularly at the regional level. This study examines the impact of Islamic philanthropic instruments, Zakat, Waqf, and Sadaqah, on women’s employment outcomes in Northern Nigeria. Using a quantitative approach, primary data were collected from 400 women beneficiaries of Islamic social finance programs and analyzed with Ordinary Least Squares (OLS) regression. The findings indicate that access to Zakat, participation in Waqf initiatives, and receipt of Sadaqah have positive and statistically significant effects on women’s employment rates. Education level and household income are also strongly associated with improved employability. These results suggest that Islamic social finance serves not only as a redistributive mechanism but also as a strategic tool to enhance women’s labor market participation and economic empowerment. This study contributes to the literature on Islamic economics and development by providing empirical evidence from an underexplored context and explicitly linking Islamic philanthropy to employment outcomes. Furthermore, the findings offer policy-relevant insights for governments, religious institutions, and philanthropic organizations in designing gender-responsive Islamic social finance initiatives to support sustainable employment and inclusive economic development